Synthesis and Characterization of Some Metals Complexes of N-[(Benzoyl Amino)-Thioxo Methyl] Proline - Waheed, Enass J (Al-Nahrain Journal of Science, 2012)
A new ligand N-[(benzoyl amino)-thioxo methyl] proline was prepared by the reaction of benzoyl isothiocyanate with proline. The ligand was characterized by FTIR, UV-Visible, and 1HNMR.Some complexes of the ligand were synthesized and characterized on the basis of their FTIR, UV-Visible spectroscopy, conductive measurements and magnetic susceptibility.From the results obtained, the following general formula has suggested for the prepared complexes is suggested [M 2+ L2].XH2OWhere:M  Mn+2, Fe+2, Co+2, Ni+2, Cu+2, Zn+2, Cd+2 and Hg+2X  3, 0, 2, 0, 4, 0, 0 and 0 L  N-[(benzoyl amino)-thioxo methyl] prolinato